Onsite Sewage Treatment and Disposal Systems: Phosphorus - Mary Lusk; Gurpal S. Toor; Tom Obreza (EDIS)
Phosphorus (P) in onsite sewage treatment and disposal systems is a concern because P can impair water quality even lower concentrations than nitrogen. This 8-page fact sheet summarizes the sources of P in septic tank effluent and the forms, concentrations, and behavior of P in the septic tank effluent and the drain field. Written by Mary Lusk, Gurpal S. Toor, and Tom Obreza and published by the UF Department of Soil and Water Science, July 2011. (Photo by Milt Putnam)